Transport features of a topological superconducting nanowire with a quantum dot: Conductance and noise - Gruñeiro, Leonel José (2023)
We study two-terminal configurations in junctions between a topological superconducting wire with spin-orbit coupling and magnetic field, and an ordinary conductor with an embedded quantum dot. One of the signatures of the Majorana zero modes in the topological phase is a quantization of the zero-bias conductance at ⁡(=0)=2⁢2/ℎ. However, the finite size of the wires and the presence of the quantum dot in the junction generate more complicated features, which lead to deviations from this simple picture. Here, we analyze the behavior of the conductance at zero and finite bias ⁡() as a function of a gate voltage applied at the quantum dot in the case of a finite-length wire. We analyze the effect of the angle between the magnetic field and the orientation associated to the spin-orbit coupling. We provide a detailed description of the spectral features of the quantum wire weakly and also strongly coupled to the quantum dot and describe the conditions to have zero-energy states in these two regimes for both the topological and nontopological phases. We also analyze the concomitant behavior of the noise. We identify qualitative features that are useful to distinguish between the topological and nontopological phases. We show that in a strongly coupled quantum dot the simultaneous hybridization with the topological modes and the supragap states of the wire mask the signatures of the Majorana bound states in both the conductance and the Fano factor.